Introducing Cultural Literacy Through Madurese Parèbhâsan Songs to 5-6 Year Old Children at Nurul Falah Kindergarten - Khosin Abdullah; Nurul Ismaiyah; Suprianto Suprianto; Siti Farida (Jurusan Tarbiyah dan Pendidikan, 2026)
This study aims to analyze the implementation of the Madurese Parèbhâsan song as a medium for introducing cultural literacy to children aged 5–6 years at Nurul Falah Kindergarten. This study employed a qualitative approach with a case study design involving one principal, one class teacher, and six children aged 5–6 years in Group B. Data were collected through observations conducted in six learning sessions, semi-structured interviews, and documentation, and were analyzed using the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The findings revealed three main themes: teacher strategies in implementing the Parèbhâsan Madura song, children’s responses to the learning activities, and supporting and inhibiting factors in its implementation. Teachers implemented the song through contextual explanations, repeated singing, interpretation of cultural meanings, and practice of èngghi-bhunten language in everyday interactions. Children showed positive responses through increased enthusiasm, participation, attention, and courage to use simple polite expressions. Supporting factors included teacher commitment, principal support, and children's enthusiasm, while the main barriers were the limited use of èngghi-bhunten in the family environment and children's greater familiarity with popular songs influenced by digital media. The findings indicate that the Madurese Parèbhâsan song can serve as a local culture-based learning medium to strengthen cultural literacy, introduce politeness values, and encourage the use of the Madurese èngghi-bhunten language among young children.